THE USE OF AIRASIA INDONESIA'S AIRCRAFT LIVERY DESIGNS TO PROMOTE TOURISM DIPLOMACY - Listianto, Karunya Saka (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
AbstractTourism plays a significant role in a nation's development, serving as a means of fostering connections and sharing information among diverse communities across borders. Moreover, it allows countries to exert their influence on a global scale through the promotion of tourism. In Indonesia, the presence of low-cost carriers such as AirAsia Indonesia has facilitated the promotion of tourism destinations and the showcasing of local cultures through innovative aircraft livery designs. This research paper adopts a qualitative case study approach to analyze the utilization of aircraft livery by AirAsia Indonesia as a form of tourism diplomacy. The data for this study was collected from the AirAsia website, focusing on four distinct liveries applied to their aircraft fleet. Through a descriptive analysis, the liveries are examined in terms of their ability to effectively communicate Indonesian destinations, cultures, and people to international audiences, thereby serving as a form of tourism diplomacy. The findings of this study suggest that AirAsia Indonesia's aircraft liveries can be regarded as an exemplary tool for tourism diplomacy, as they successfully convey Indonesia's unique tourism offerings and identities on the global stage.Keywords: Aircraft Livery; AirAsia Indonesia; Tourism DiplomacyAbstrakPeran pariwisata bagi suatu negara sangatlah penting dalam hal pembangunan, karena melalui pariwisata dapat memfasilitasi terbentuknya hubungan dan pertukaran informasi antar berbagai komunitas lintas batas negara. Lebih lanjut, pariwisata memberikan kesempatan bagi negara untuk mempengaruhi skala global melalui promosi destinasi pariwisata. Di Indonesia, kehadiran maskapai penerbangan berbiaya rendah seperti AirAsia Indonesia telah memudahkan promosi destinasi wisata dan pengenalan budaya lokal melalui rancangan livery pesawat yang inovatif. Penelitian ini menggunakan metode studi kasus kualitatif untuk menganalisis pemanfaatan livery pesawat oleh AirAsia Indonesia sebagai bagian dari diplomasi pariwisata. Data penelitian diperoleh dari situs web AirAsia Indonesia, dengan fokus pada empat livery pesawat yang berbeda. Melalui analisis deskriptif, keempat livery tersebut dievaluasi dari kemampuannya untuk mengkomunikasikan destinasi, budaya, dan masyarakat Indonesia kepada audiens internasional, yang merupakan bentuk diplomasi pariwisata. Temuan penelitian mengindikasikan bahwa livery pesawat AirAsia Indonesia dapat disebut sebagai alat diplomasi pariwisata yang efektif, karena berhasil memperkenalkan daya tarik pariwisata unik Indonesia ke kancah global.Kata Kunci: Livery Pesawat; AirAsia Indonesia; Diplomasi Pariwisata